Pre-hispanic wetland irrigation and metallurgy in the South Andean Altiplano (Intersalar Region, Bolivia, XIVth and XVth century CE) - Guédron, Stéphane (2024)
The high-altitude Andean Altiplano has been subject to abrupt climate changes during the Holocene. The resulting impact on the hydrological cycle has obliged ancient societies to adapt and develop strategies to face droughts and sustain agropastoral activities. Here, we present the results of archaeological prospections together with the biogeochemical characterization of a well-dated core collected at Saitoco wetland in the arid southern Altiplano (Intersalar Region, Bolivia). Archaeological survey allowed the mapping of a network of channels collecting water from the surrounding mountains to the wetland, and the presence of small copper mines and metallurgical installations. Traces and major element concentrations and accumulation rates, together with elemental and isotopic characterization of organic matter (OM) (i.e., Corg and δ13Corg) in the wetland core have been used to document the evolution of the landscape in relation to climatic and anthropogenic pressure. While OM, bromine (Br), selenium (Se) and mercury (Hg) data were used to assess the variability of precipitations during the Late Holocene (4.2 ka BP to the present), local and regional mining activities have been reconstructed through the variations of lead (Pb), copper (Cu), and antimony (Sb). Our results show an abrupt change in OM composition during the 14th and 15th century CE, characterized by an abrupt shift in δ13Corg synchronous with a rise in Br, Se and Hg, testifying for the waterlogging of the wetland during a known arid period in the region. This change is attributed to anthropogenic transformation of the landscape through the irrigation of the wetland by channeling streams from the surrounding mountains. At the same time, a mining pollution signal was recorded supporting local Cu mining and metallurgy. The mining signal then reached its maximum values during the Inca and Colonial periods, which matches with reported enhanced mining activities in the region. From the colonial era onward, the wetland progressively dried up, likely resulting from the abandonment of the site. Through the combination of a biogeochemical record and archaeological prospections, this study provides evidences that societies of the arid Intersalar region have transformed their landscape and developed wetland irrigation and mining during the arid 14th and 15th century CE Period.